Hybrid FEM-PML and FEM-MoL solutions of electromagnetic scattering problems - Xiao, Ying (2008)
In this study, several new perfectly matched layers are developed, an efficient approach based on vectorial edge finite element method (FEM) and optimal selec-tion of newly proposed and existence perfectly matched layers (PMLs) has been developed for scattering and radiating problems of arbitrary structure, such as microstrip antenna on arbitrary coated or conducting host objects.